Interpersonal relationships in Hungary – an overview - Albert, Fruzsina; Dávid, Beáta (METSZETEK Társadalomtudományi Folyóirat, 2018)
Our paper aims to demonstrate that social structure has significant impact on the formation ofinterpersonal relations. We review and analyse the characteristics of ego-centric interpersonalnetworks of Hungarians based on data from nationally representative adult population surveysbetween the mid-1980’s up to 2015. We focus especially on core discussion networks, friendshipties and weak ties and analyse how the transition to market economy influenced interpersonalrelationships. As expected, the large-scale social changes brought about by the transitionchanged interpersonal networks as well. During the first decade of the transition (in the 1990’s)one could not witness a significant change of personal networks, nonetheless the adaptationprocess was easier for people supported by strong, traditional family ties. Non-kin ties, especiallyfriendships seem to gain significance at the expense of kin relationships. Overall, resourcesavailable through weak ties seem to be decreasing.